Development of innate immune memory by non-immune cells during Staphylococcus aureus infection depends on reactive oxygen species - Chaumond, Emmanuel; Peron, Sandrine; Daniel, Nathalie; Le Gouar, Yann; Guédon, Éric; Williams, David L.; Le Loir, Yves; Jan, Gwénaël; Berkova, Nadia (Frontiers in Immunology, 2023)
Introduction The mechanisms underlying innate immune memory (trained immunity) comprise epigenetic reprogramming of transcriptional pathways associated with alterations of intracellular metabolism. While the mechanisms of innate immune memory carried out by immune cells are well characterized, such processes in non-immune cells, are poorly understood. The opportunistic pathogen, Staphylococcus aureus, is responsible for a multitude of human diseases, including pneumonia, endocarditis and osteomyelitis, as well as animal infections, including chronic cattle mastitis that are extremely difficult to treat. An induction of innate immune memory may be considered as a therapeutic alternative to fight S. aureus infection. Methods In the current work, we demonstrated the development of innate immune memory in non-immune cells during S. aureus infection employing a combination of techniques including Enzyme-linked immunosorbent assay (ELISA), microscopic analysis, and cytometry. Results We observed that training of human osteoblast-like MG-63 cells and lung epithelial A549 cells with β-glucan increased IL-6 and IL-8 production upon a stimulation with S. aureus, concomitant with histones modifications. IL-6 and IL-8 production was positively correlated with an acetylation of histone 3 at lysine 27 (H3K27), thus suggesting epigenetic reprogramming in these cells. An addition of the ROS scavenger N-Acetylcysteine, NAC, prior to β-glucan pretreatment followed by an exposure to S. aureus, resulted in decreased IL-6 and IL-8 production, thereby supporting the involvement of ROS in the induction of innate immune memory. Exposure of cells to Lactococcus lactis resulted in increased IL-6 and IL-8 production by MG-63 and A549 cells upon a stimulation with S. aureus that was correlated with H3K27 acetylation, suggesting the ability of this beneficial bacterium to induce innate immune memory. Discussion This work improves our understanding of innate immune memory in non-immune cells in the context of S. aureus infection. In addition to known inducers, probiotics may represent good candidates for the induction of innate immune memory. Our findings may help the development of alternative therapeutic approaches for the prevention of S. aureus infection.